Assuan, Ägypten Regionale Siedlungsnetzwerke – Geoarchäologischer Survey nördlich von Assuan - Klose, Ilka (e-Forschungsberichte des DAI, 2023)
The appearance of the Nile riverbanks north of Aswan is the result of a long evolution in which geological, climatological, geomorphological and anthropic factors played a role. In order to disentangle this evolution, a surface survey and shallow drillings were conducted on the eastern shore of the Nile, precisely in the area of the villages Abu el-Rish Qibli, Abu el-Rish Bahari and the former island Geziret Bahrif. Results show amongst others a continuous and up to 3 m thick occupation layer of the Roman and Medieval Period which is covered by more recent accumulations of Nile mud.